2015
DOI: 10.3390/ijerph120404060
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Workers’ Knowledge, Attitudes and Practices on Tobacco Use in Economically Disadvantaged Dominican Republic Communities

Abstract: Tobacco use is increasing globally, particularly in low and middle-income countries like the Dominican Republic (DR) where data have been lacking. Health care worker (HCW) interventions improve quit rates; asking patients about tobacco use at each visit is an evidence-based first step. This study provides the first quantitative examination of knowledge, attitudes and practices of DR HCWs regarding tobacco use. All HCWs (N = 153) in 7 economically disadvantaged DR communities were targeted with anonymous survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
2
11
0
1
Order By: Relevance
“…We continue to report findings from PDT studies elsewhere (e.g., Chin, et al in press; Dozier et al, 2006, 2009, 2014; Lando et al 2010; McIntosh, et al, 2008; Ossip-Klein, et al 2008; Ossip, et al; 2013, 2015; Prucha, et al 2015; Torres, et al 2011, 2014; Wipfli, et al 2008). The current paper will report on lessons learned from implementing this US-DR partnered research.…”
Section: Research Rationale/descriptionmentioning
confidence: 87%
See 2 more Smart Citations
“…We continue to report findings from PDT studies elsewhere (e.g., Chin, et al in press; Dozier et al, 2006, 2009, 2014; Lando et al 2010; McIntosh, et al, 2008; Ossip-Klein, et al 2008; Ossip, et al; 2013, 2015; Prucha, et al 2015; Torres, et al 2011, 2014; Wipfli, et al 2008). The current paper will report on lessons learned from implementing this US-DR partnered research.…”
Section: Research Rationale/descriptionmentioning
confidence: 87%
“…For example, our data indicated that most healthcare providers were unsure whether patients wanted their advice to quit using tobacco (Prucha et al, 2015), yet 87% of tobacco users reported that this would help. Our investigators shared these results at multiple professional society and healthcare provider workshops and conferences, including trainings for public health workers through the Health Ministry.…”
Section: Establishing An Infrastructure For Tobacco Cessation Researcmentioning
confidence: 94%
See 1 more Smart Citation
“…Varios estudios recientes demuestran que el personal de la salud no se ve a sí mismo como un ejemplo, mostrando diferentes porcentajes que oscilan entre 44.3% y el 57.89% (16,19,31); mientras que en la implementación del GHPSS se reportó que en países como Cuba, Guatemala y Panamá el 100% de los encuestados está de acuerdo con el rol médico de aconsejar -(3234); por su parte, en Laos el 94.9% de los médicos fumadores y el 97.7% de los exfumadores creen que las posibilidades de que un paciente cese el hábito aumentan si el médico lo aconseja (17).…”
Section: Discussionunclassified
“…The problem is multi-layered: many LMICs have high rates of tobacco use by physicians and other healthcare providers (Abdullah, Qiming, Pun, Stillman, & Samet, 2013, Abdullah et al, 2014; Asfar, Al-Ali, Ward, Vander Weg, & Maziak, 2011), which make them reluctant to champion their patients’ quit attempts. Beyond this motivational issue, many physicians are skeptical that patients want their advice to quit smoking (Ossip et al, 2016; Prucha et al, 2015), do not view cessation as part of their jobs (Dozier et al, 2009; Tee, & Hairi, & Hairi, 2012), and misunderstand the harms of tobacco (Abdullah & Husten, 2004; Asfar et al, 2011; Dogar, Elsey, Khanal, & Siddiqi, 2016; Lando, 2016). …”
mentioning
confidence: 99%